2016
DOI: 10.15406/mojor.2016.05.00184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supervised Training Compared to Unsupervised Training on Physical Activity, Muscular Endurance, and Cardiovascular Parameters

Abstract: Evidence has suggested that among untrained individuals, supervised exercise interventions may elicit greater health benefits and long-term exercise adherence compared to unsupervised exercise interventions.Purpose: This study focused on determining the effectiveness of a five-month supervised exercise intervention compared to a five-week unsupervised duration at a university work-site for faculty and staff members on physical activity behavior, muscular endurance, and cardiovascular health.Methods: An exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…While unsupervised home exercises may be more accessible for patients, this review found that adherence and outcomes were more favourable when exercises were performed in a supervised setting. Exercise conducted in a supervised setting enables a structured program, promotes motivation through visual feedback and encourages participants to achieve the minimum required dose of exercise [ 50 ]. However, supervised exercise programs also present with barriers including difficulty in the initial set up of a program, costs, availability of classes and limits on the number of participants allowed to engage per class [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…While unsupervised home exercises may be more accessible for patients, this review found that adherence and outcomes were more favourable when exercises were performed in a supervised setting. Exercise conducted in a supervised setting enables a structured program, promotes motivation through visual feedback and encourages participants to achieve the minimum required dose of exercise [ 50 ]. However, supervised exercise programs also present with barriers including difficulty in the initial set up of a program, costs, availability of classes and limits on the number of participants allowed to engage per class [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study also demonstrated that supervised training is more effective for PA than is unsupervised training. 50 Because most interventions for survivors are conducted in the community, independently initiating PA after they are discharged from the hospital may be challenging. Therefore, the supervised sessions in the PA program are needed.…”
Section: Body Mass Indexmentioning
confidence: 99%
“…In another study, Fennell et al [43] found a significant increases in level of physical activity and muscular endurance when training intervention was supervised by exercise professionals; however, when receiving only recommendations for the practice of physical activity without supervision, the participants returned to baseline scores, losing the acquired effects. Probably these results can be explained by motivational factors [44,45].…”
Section: Discussionmentioning
confidence: 97%